Effect of Urate-Lowering Therapy on the Progression of Kidney Function in Patients With Asymptomatic Hyperuricemia: A Systematic Review and Meta-Analysis - Zhang, Lin; An, Kang; Mou, Xingyu; Zhang, Mei; Su, Qiaoli; Li, Shuangqing (Frontiers in Pharmacology, 2022)
Background: Hyperuricemia is involved in the risk of chronic kidney disease (CKD). However, whether uric acid lowering therapy (ULT) can bring benefits of the progression of kidney function in patients with asymptomatic hyperuricemia is still on controversial. We conducted a systematic review and meta-analysis to evaluate the effect of ULT on the progression of kidney function in asymptomatic hyperuricemia patients. Methods: The MEDLINE, EMBASE and Cochrane databases were searched without language, national or ethnic restrictions for randomized controlled trials published prior to November 30, 2020, that compared ULT with controlled therapy in patients with asymptomatic hyperuricemia. Results: 11 studies were included for qualitative synthesis. ULT did not ameliorate eGFR slopes (WMD 0.36 mL/min/1.73 m2 per year, 95% CI: -0.29, 1.01), or lead to reductions in kidney events (RR 1.26; 95% CI: 0.80, 2.00) or all-cause mortality (RR 1.00; 95% CI: 0.65, 1.55), although ULT resulted in the decrease in serum uric acid levels (WMD -2.73 mg/dl; 95% CI: -3.18, -2.28) and lowered the incidence of gout attack (0.9% vs 2.7%, RR 0.38; 95% CI: 0.17, 0.86). Conclusions: In patients with asymptomatic hyperuricemia, ULT did not decay the progression of kidney function. Long-term and larger sample studies are needed to verify the results.